2022
DOI: 10.1302/2633-1462.310.bjo-2022-0082.r1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tibial alignment parameters based on clinically relevant anatomical landmarks

Abstract: Aims Accurate identification of the ankle joint centre is critical for estimating tibial coronal alignment in total knee arthroplasty (TKA). The purpose of the current study was to leverage artificial intelligence (AI) to determine the accuracy and effect of using different radiological anatomical landmarks to quantify mechanical alignment in relation to a traditionally defined radiological ankle centre. Methods Patients with full-limb radiographs from the Osteoarthritis Initiative were included. A sub-cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…AI image recognition may soon be a highly sought-after application in orthopaedics, corroborated in a study by Jang et al 47 where CNNs were reported to identify bone and soft-tissue landmarks as objects on radiographs. Additionally, more accurate calculations using the DL model for knee alignment may provide the potential for preoperative planning in total knee arthroplasty (TKA).…”
Section: Image Recognition and Diagnosticsmentioning
confidence: 72%
See 2 more Smart Citations
“…AI image recognition may soon be a highly sought-after application in orthopaedics, corroborated in a study by Jang et al 47 where CNNs were reported to identify bone and soft-tissue landmarks as objects on radiographs. Additionally, more accurate calculations using the DL model for knee alignment may provide the potential for preoperative planning in total knee arthroplasty (TKA).…”
Section: Image Recognition and Diagnosticsmentioning
confidence: 72%
“…Additionally, more accurate calculations using the DL model for knee alignment may provide the potential for preoperative planning in total knee arthroplasty (TKA). 47 However, several limitations such as the established ground truths, radiograph quality, alignment, or rotation indicate the variability and, as such, these methods are not yet employed in preoperative planning for TKA. 47 …”
Section: Image Recognition and Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early work has suggested disproportionate accuracy in prediction of final femoral component sizing although algorithm refinements are likely to show improved utility for tibial component sizing also [ 67 ]. Coupled with high-resolution preoperative imaging, AI applications have shown value in identifying anatomical landmarks to guide construct alignment [ 69 ], which may benefit the precision obtained intraoperatively.…”
Section: Methodsmentioning
confidence: 99%
“…3,4 This field is growing rapidly as the techniques are applied widely across orthopaedics. [5][6][7][8][9][10] Interpretation of AI data requires that some of the core principles of EBM are re-framed. Currently, AI research predominantly consists of retrospective analysis of datasets with an exploratory approach, which may be seen as a lower level of evidence.…”
Section: Introductionmentioning
confidence: 99%